The Architect as Producer: Hannes Meyer and the Proletarianisation of the Western Architect - Amir Djalali (Footprint)
With the foundation of the Bauhaus, Walter Gropius advocated an end to the division between arts and crafts. Contrary to the idea of architecture as art, the programme of the school aimed to assimilate architecture with industry in order to satisfy collective social needs. Yet, despite this programmatic declaration, such a project was realised only after Gropius’ departure from the Bauhaus, under the controversial directorship (1927–1930) of the Swiss architect Hannes Meyer. Meyer achieved unprecedented success both in terms of academic production and financial performance. Yet his realisations were paralleled by the leftist radicalisation of the school’s politics: Meyer transformed the workshops into factory production units and the students into industrial workers. Eventually, the politicisation of the school cost Meyer his office and a negative reputation in historical records that still holds today. This article posits that Meyer achieved his success at the Bauhaus not despite his radical allegiance, but precisely because of it. The realism of Meyer’s strategy is evaluated through his capacity to anticipate many developments in the organisation of architectural production. In particular, his critique of intellectual labour in architecture is confronted with the contemporary proletarisation of architects in the Western world.